ChemInform Abstract: Pd(quinox)‐Catalyzed Allylic Relay Suzuki Reactions of Secondary Homostyrenyl Tosylates via Alkene‐Assisted Oxidative Addition. Issue 43 (21st October 2014) - Stokes, Benjamin J.; Bischoff, Amanda J.; Sigman, Matthew S.
Abstract Mechanistic studies suggest that the oxidative addition requires direct alkene involvement.